Technoeconomic Assessment of Electric Vehicle Battery Disassembly-Challenges and Opportunities From a Robotics Perspective - Jamie Hathaway; Cesar Alan Contreras; Mohammed Eesa Asif; Rustam Stolkin; Alireza Rastegarpanah (IEEE Access)
The rapid shift towards electric vehicles (EVs) demands effective end-of-life strategies for lithium-ion batteries (LIBs), necessitating examining recycling methodologies, particularly the disassembly process. This study presents a technoeconomic analysis of EV battery disassembly, focusing on incorporating robotics to address challenges and capitalize on opportunities. Based on the case study of the Mitsubishi Outlander PHEV battery pack, we identify the most labor and cost-intensive components and introduce a structured approach to evaluate automating disassembly tasks. Classifying tasks based on their automation potential, we find 57% of pack-to-module (P2M) tasks readily automatable, with an additional 24% requiring minimal human intervention. Incorporating this into an analysis of task feasibility, level of automation and robot time efficiency, we establish a roadmap towards robotizing the disassembly process based on human-robot colllaboration, demonstrating a 12.85% increase in net annual revenue and 43.75% reduction in disassembly cost with current level of task feasibility. Our findings indicate a long-term roadmap towards increasing level of automation, while surmounting feasibility of complex disassembly tasks remains an unsolved challenge.